The Dutch voter, 1972-1973. National electoral data project. [Transl. from the Dutch] (Institute for Political Sciencee, [Catholic University], 1974)
With index and tabs. Original title: Nationaal kiezersonderzoek 1972/1973. Een systematische classificatie van de gegevens: een SPSS- en card-image file.